Community-Level Pharmaceutical Interventions to Reduce the Risks of Polypharmacy in the Elderly: Overview of Systematic Reviews and Economic Evaluations - Soler, Orenzio; Barreto, Jorge Otávio Maia (Frontiers in Pharmacology, 2019)
Background: Patients over 65 years of age taking multiple medications face several risks, and pharmaceutical interventions can be useful to improve quality of care and reduce those risks. However, there is still no consensus on the effectiveness of these interventions aimed at promoting changes in clinical, epidemiological, economic, and humanistic outcomes for various service delivery, organizational, financial, and implementation-based interventions. The objective of this overview of systematic reviews was to summarize evidence on the effectiveness of community-level pharmaceutical interventions to reduce the risks associated with polypharmacy in the population over 65 years of age. Method: This overview used a previously described protocol to search for systematic review articles, with and without meta-analysis, and economic evaluations, without any language or time restrictions, including articles published up to May 2018. The following databases were searched: the Cochrane Library, Epistemonikos, Health Evidence, Health Systems Evidence, Virtual Health Library, and Google Scholar. The basic search terms used were “elderly,” “polypharmacy,” and “pharmaceutical interventions.” The findings for outcomes of interest were categorized using a taxonomy for health policies and systems. Equity-related questions were also investigated. The studies were evaluated for methodological quality and produced a narrative synthesis. Results: A total of 642 records were retrieved: 50 from Health Evidence, 197 from Epistemonikos, 194 from Cochrane, 116 from Health Systems Evidence, and 85 from the Virtual Health Library. Of these, 16 articles were selected: 1 overview of systematic reviews, 12 systematic reviews, and 3 economic evaluations. There is evidence of improvement in clinical, epidemiological, humanistic, and economic outcomes for various types of community-level pharmaceutical interventions, but differences in observed outcomes may be due to study designs, primary study sample sizes, risk of bias, difficulty in aggregating data, heterogeneity of indicators and quality of evidence included in the systematic reviews that were assessed. It is necessary to optimize the methodological designs of future primary and secondary studies. Conclusion: Community-level pharmaceutical interventions can improve various clinical, epidemiological, humanistic and economic outcomes and potentially reduce risks associated with polypharmacy in the elderly population.